Answer:
A) (–4, 8)
Explanation:
to solve this system of equation
we will say let
y = 2x + 16 ............................. equation 1
2x – 7y = –64............................ equation 2
substitute equation 1 into equation 2
2x – 7y = –64............................ equation 2
2x - 7( 2x + 16) = -64
2x - 14x -112 = -64
combine the like terms
2x - 14x = -64 +112
-12x = 48
divide both sides by the coefficient of x
-12x/-12 = 48/-12
x = -4
put the value of x = -4 into equation 1
y = 2x + 16 ............................. equation 1
y = 2(-4) + 16
y = -8 + 16
y = 8
therefore the value of x and y is -4 and 8 respectively